Investigations on Microstructure and Mechanical Properties of the Cu/Pb-free Solder Joint Interfaces - Zhang, Qingke (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This thesis presents a series of mechanical test methods and comprehensively investigates the deformation and damage behavior of Cu/Pb-free solder joints under different loading conditions. The fracture behavior of Pb-free joint interfaces induced by stress, deformation of solder and substrate are shown, the shear fracture strength of the Cu6Sn5 IMC is measured experimentally for the first time, and the dynamic damage process and microstructure evolution behavior of Pb-free solder joints are revealed intuitively. The thesis puts forward the argument that the local cumulative damage is the major cause of failure in solder joints. The research results provide the experimental and theoretical basis for improving the reliability of solder joints.